Employee Performance Determinants in A Private Electrical Services Firm: The Effects of Work Stress, Organizational Culture, and Self-Efficacy - Pande Ketut Aditya Pratama; I Gede Rihayana; I Komang Oka Permadi (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Employee performance is a critical factor in maintaining operational effectiveness and competitiveness in private service firms, especially firms that depend on technical reliability, work discipline, and timely task completion. This study aims to examine the effects of work stress, organizational culture, and self-efficacy on employee performance at PT. Bumi Sentosa, a private electrical services firm in Denpasar, Bali. This study applied a quantitative explanatory approach. The population consisted of 33 employees, and all employees were selected as respondents using a saturated sampling technique. Data were collected through observation, interviews, documentation, and questionnaires. The data were analyzed using multiple linear regression. The findings show that work stress has a negative and significant effect on employee performance, while organizational culture and self-efficacy have positive and significant effects. These results indicate that employee performance can improve when the company reduces excessive work pressure, strengthens shared work values, and develops employees’ confidence in completing their duties. This study provides practical insight for human resource management in small private technical service firms and supports more focused performance improvement policies.